2004
DOI: 10.1186/1471-2105-5-58
|View full text |Cite
|
Sign up to set email alerts
|

Use of a structural alphabet for analysis of short loops connecting repetitive structures

Abstract: Background: Because loops connect regular secondary structures, analysis of the former depends directly on the definition of the latter. The numerous assignment methods, however, can offer different definitions. In a previous study, we defined a structural alphabet composed of 16 average protein fragments, which we called Protein Blocks (PBs). They allow an accurate description of every region of 3D protein backbones and have been used in local structure prediction. In the present study, we use this structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…It corroborates previous observations that have already noted a high divergence of this method with every other SSAMS. [14] SSAMS that assigns less α-helix (mean value = 36.74%) assigns more β-strand (mean value = 22.25%). Analysis of coil frequency gives two major clusters above and below 17%.…”
Section: Descriptionmentioning
confidence: 99%
“…It corroborates previous observations that have already noted a high divergence of this method with every other SSAMS. [14] SSAMS that assigns less α-helix (mean value = 36.74%) assigns more β-strand (mean value = 22.25%). Analysis of coil frequency gives two major clusters above and below 17%.…”
Section: Descriptionmentioning
confidence: 99%
“…Our earlier work on PBs have shown that PBs are effective in describing and predicting conformations of long fragments (Benros, et al, 2006; Benros, et al, 2009; Bornot, et al, 2009; de Brevern, et al, 2007; de Brevern and Hazout, 2001; de Brevern and Hazout, 2003; de Brevern, et al, 2002) and short loops (Fourrier, et al, 2004; Tyagi, et al, 2009; Tyagi, et al, 2009), analyzing protein contacts (Faure, et al, 2008), in building a transmembrane protein (de Brevern, 2005; de Brevern, et al, 2009), and in defining a reduced amino acid alphabet to aid design of mutations (Etchebest, et al, 2007). This reduced amino acid alphabet was recently proved suitable for predicting protein families or sub-families and secretory proteins of P. falciparum (Zuo and Li, 2009; Zuo and Li, 2009).…”
Section: Protein Blocksmentioning
confidence: 99%
“…A website, LocPred (http://www.dsimb.inserm.fr/~debrevern/LOCPRED/), which includes most of the tools developed so far, is available to perform these predictions (de Brevern, et al, 2004). Predictions were also performed with the SWs (de Brevern, et al, 2007; de Brevern, et al, 2002) and specifically for short loops (Fourrier, et al, 2004; Tyagi, et al, 2009). …”
Section: Applicationsmentioning
confidence: 99%
“…The template-free [74-81, 83, 84] methods reported accuracies from 82 to 87%, a substantial improvement over the fourth-generation accuracy of 80%. The theoretical 3-label accuracy limit is 90-95% [1,30,72,82,85,86], based on the rate at which different programs such as DSSP and Stride [87] assign the same secondary structure to experimental coordinates.…”
Section: Introductionmentioning
confidence: 99%